A semiotic analysis of ‘Individualism’ and ‘Collectivism’: The Global Bersih 3.0 Website - Mokhtar, Aida (UNIMAP, 2015)
In 2012, one of the biggest rallies in the past decade took place in Malaysia calling for electoral reform (BBC NEWS Asia 2012). This rally took place amidst the ambience of the 13th General Election campaigning. The involvement of Bersih in the rally spurred my study of its webpage through a semiotic analysis with focus given to cultural values.